Inovasi Aplikasi “Telunjuk Sakti” dalam Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wonogiri - Yuli Astuti; Is Hadri Utomo (Jurnal Mahasiswa Wacana Publik, 2021)
This research’s purpose is to describe the typology of innovation in the "telunjuk sakti" application in population administration services at the Department of Population and Civil Registration of Wonogiri Regency, which is studied with the innovation typology theory according to Perry (2010). This type of research is descriptive qualitative, with data collection techniques using interviews. Determination of informants using purposive sampling and snowball sampling techniques. The validity data used source triangulation method. The analysis data technique used the interactive model of Miles & Huberman's analysis. The results showed that there were six typologies of innovation in the "telunjuk sakti" application. Of the six innovation typologies, there are three innovation typologies that meet the overall criteria, namely product innovation which is a new product that is disseminated through direct and indirect socialization and is adapted to current needs; in service innovation there is a renewal of the service model using mobile phones; and on systemic innovation to cooperation in terms of utilization of population data and in terms of services. Meanwhile, the other three typologies of innovation only fulfill some of the criteria, namely in process innovation there is a procedure update; in the conceptual typology there is a renewal of the employee mindset; and in policy innovation, there are strategies to support employee mindset renewal. Unfulfilled criteria, namely in process innovation there is no renewal of the organizational structure; in conceptual innovation there is no renewal of the mission and purpose of innovation services; and in policy innovation there is no strategy to support the renewal of the mission and service goals of innovation.